2006
DOI: 10.1266/ggs.81.349
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of wheat alternative oxidase gene Waox1a alters respiration capacity and response to reactive oxygen species under low temperature in transgenic Arabidopsis

Abstract: Under low temperature conditions, the cytochrome pathway of respiration is repressed and reactive oxygen species (ROS) are produced in plants. Mitochondrial alternative oxidase (AOX) is the terminal oxidase responsible for the cyanideinsensitive and salicylhydroxamic acid-sensitive respiration. To study functions of wheat AOX genes under low temperature, we produced transgenic Arabidopsis by introducing Waox1a expressed under control of the cauliflower mosaic virus (CaMV) 35S promoter in Arabidopsis thaliana .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…3B). A similar increase of the alternative pathway activity occurred under abiotic stress conditions such as low temperature (Purvis and Shewfelt, 1993;Vanlerberghe et al, 2002;Sugie et al, 2006).…”
Section: Respiration Capacities In the Necrosis Linesmentioning
confidence: 59%
See 1 more Smart Citation
“…3B). A similar increase of the alternative pathway activity occurred under abiotic stress conditions such as low temperature (Purvis and Shewfelt, 1993;Vanlerberghe et al, 2002;Sugie et al, 2006).…”
Section: Respiration Capacities In the Necrosis Linesmentioning
confidence: 59%
“…We previously isolated two non-homoeologous genes, Waox1a and Waox1c, encoding the AOX proteins from common wheat (Takumi et al, 2002). WAOX1a alleviates oxidative stress when the cytochrome pathway of respiration is inhibited under low temperature stress conditions (Sugie et al, 2006). The aim of the present study was to clarify the AOX function in necrosis.…”
Section: Introductionmentioning
confidence: 95%
“…It was observed that Arabidopsis plants expressing antisense AOX1a showed greater susceptibility to drought [12], low temperature [13], and high light [6] compared with wild-type plants. Furthermore, Arabidopsis plants constitutively overexpressing AOX1a gene had greater tolerance to high salt and low temperature stress than wild-type plants [14,15].…”
Section: Expression Of Aox Genes Under Abiotic Stressesmentioning
confidence: 98%
“…Notable ones include prevention of overreduction of mitochondrial electron transport chain under conditions when growth is restricted such as low temperature (Purvis and Shewfelt, 1993), drought (Collier and Commins, 1992), high salinity (Hilal et al, 1998) and low supply of minerals (Parsons et al, 1999). AOX may also function in the maintenance of constant energy charge and in scavenging reactive oxygen species in mitochondria during growth under variable environment conditions (Moore et al, 2002) as well as in apoptosis and genetic necrosis (Vanlerberghe et al, 2002;Marechal and Baldan, 2002;Mizuno et al, 2005;Sugie et al, 2007).…”
Section: Introductionmentioning
confidence: 99%